Acute Pulmonary Embolism Caused by Abdominal Pannus Retraction in an Awake Patient in the Operating Room: A Case Report. Issue 1 (January 2022) - Rier, Alex S.; Subramani, Sudhakar; Ravindranath, Sapna; Singhal, Arun; Hanada, Satoshi
Abstract : We present a 67-year-old woman who was hemodynamically stable with radiographic evidence of saddle pulmonary embolism (PE) in the main pulmonary artery and mobile thrombus in the right heart. Endovascular thrombectomy was scheduled under general anesthesia. Before anesthesia induction, femoral vessel access was planned under local anesthesia in case emergent cardiopulmonary bypass (CPB) was needed. Immediately after abdominal pannus retraction was applied for better groin access, the patient developed cardiac arrest, and advanced cardiovascular life support (ACLS) protocol was initiated. Transesophageal echocardiography (TEE) confirmed acute massive PE. CPB was emergently established. Surgical embolectomy was conducted with successful outcome. Abstract : Supplemental Digital Content is available in the text.